Correction: Corrigendum: Neuronal IFN-beta–induced PI3K/Akt-FoxA1 signalling is essential for generation of FoxA1+Treg cells - Yawei Liu (Nature Portfolio, 2017)
Nature Communications 8: Article number: 14709 (2017); Published 24 April 2017; Updated 22 May 2017 The affiliation details for Marco Prinz are incorrect in this Article. The correct affiliation details for this author are given below: Institute of Neuropathology, Faculty of Medicine, University of Freiburg, Freiburg 79106, Germany.